ANALISIS PENYEBAB KERUSAKAN DINI PADA PERKERASAN JALAN PARIT IV SEI SAREN STA. 3 + 580 – STA. 4 + 211 KABUPATEN TANJUNG JABUNG BARAT PROVINSI JAMBI - Daffano, Rd M Syifa; Gusmulyani, Gusmulyani; Dewi, Selpa (Ensiklopedia of Journal, 2025)
Roads that are damaged before reaching their design life often occur in various regions and have an impact on reducing comfort and public trust in the quality of infrastructure. One case occurred on the Parit IV Sei Saren Road Section in West Tanjung Jabung Regency, Jambi Province, which experienced surface deformation in less than one year after upgrading. This study aims to identify the type of damage, evaluate its main causes, and assess the effectiveness of the treatment that has been carried out. The research approach is descriptive qualitative with data collection techniques through visual surveys, interviews with contractors, questionnaires, and daily traffic surveys. The survey results showed that the dominant damage was in the form of waves (shoving) on the pavement surface with a total area of 229.90 m² (0.91% of the total surface). From the analysis, it was found that the actual traffic load was much lower than the plan due to the prohibition of heavy vehicles. Therefore, indications of the main cause of damage are more directed at the implementation aspect, especially at the binding and compaction stages of the layers, which were considered less than optimal by some respondents. Although tack coat application was initially suspected as a contributing factor, test results indicated that the volume met specifications, necessitating further testing to ensure the bond strength between the layers. The proposed treatment involved patching caps, which involve repairs to the top or surface layer, as field inspections revealed no signs of damage to the underlying layer. This research underscores the importance of quality control during project implementation and encourages further studies using a broader approach to methods and causal variables to prevent future premature damage.Keywords: Premature Damage, Road Pavement, Types of Road Damage, LHR Survey, Quality Control.